Dispersant for lithium ion batteries and method for producing same, positive electrode slurry and method for producing same, and lithium ion battery and method for producing same
A dispersant with solvent-philic and highly adhesive monomer units enhances dispersion and adhesion in lithium ion batteries, addressing the limitations of conventional dispersants by maintaining active material proportion and improving manufacturing efficiency.
Patent Information
- Application Number
- JP2023532446
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-11-28
- Filing Date
- 2021-11-25
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2041-11-25
AI Technical Summary
Conventional dispersants for lithium ion batteries, such as polyvinylpyrrolidone and polyacrylamide, have limited dispersion ability and are used in large amounts, reducing the mass proportion of positive electrode active material and lowering the specific capacity of the battery.
A dispersant comprising structural units derived from solvent-philic, conjugated diene, and highly adhesive monomers, providing excellent dispersion and adhesion properties, allowing for a reduced amount of adhesive use while maintaining the mass proportion of the positive electrode active material.
The dispersant achieves high dispersion of cathode active materials and conductive agents, maintaining the specific capacity of the battery and improving manufacturing efficiency without reducing the mass proportion of the positive electrode active material.
Smart Images

Figure 0007618805000001
Abstract
Description
[Technical field]
[0001] (Priority information) This application claims priority to Chinese Patent Application No. 202011361699.6, filed with the State Intellectual Property Office of the People's Republic of China on November 28, 2020, entitled "Dispersant for lithium ion batteries and manufacturing method thereof, positive electrode slurry, positive electrode plate and lithium ion battery," the entire contents of which are incorporated herein by reference.
[0002] The present application relates to the technical field of lithium ion batteries, and more particularly to a dispersant for lithium ion batteries and a method for producing the same, a positive electrode slurry, and a lithium ion battery. [Background technology]
[0003] The components of the positive electrode slurry of a lithium ion battery mainly include a positive electrode active material, a conductive agent, an adhesive and a solvent. As the requirements for battery performance increase, the requirements for the process manufacturing process of the positive electrode slurry also increase. On the one hand, it is necessary to improve the dispersion effect of the positive electrode active material and the conductive agent in the positive electrode slurry to improve the uniformity of the positive electrode plate, and on the other hand, it is necessary to improve the solid content of the positive electrode slurry to improve the coating performance of the positive electrode slurry and improve the yield and production capacity of the positive electrode plate. Adding a dispersion assistant to the positive electrode slurry is the mainstream method in the industry to improve the dispersion effect of the positive electrode slurry.
[0004] There are only a few types of dispersants available for conventional lithium-ion batteries, mainly polyvinylpyrrolidone (PVP), polyacrylamide (PAM), etc. However, these dispersants have limited dispersion ability for the positive electrode slurry and generally require a large amount of addition, which accordingly reduces the mass ratio of the positive electrode active material in the positive electrode material layer formed by the positive electrode slurry, and further reduces the specific capacity of the battery. Therefore, in order to achieve a good slurry dispersion effect with a small amount of dispersant used, it is necessary to develop a dispersant with good dispersion ability for the positive electrode slurry. Summary of the Invention
[0005] In view of this, the embodiments of the present application provide a dispersant for lithium ion batteries and a manufacturing method thereof, a positive electrode slurry, and a lithium ion battery, and the dispersant for lithium ion batteries can combine the functions of an adhesive and a dispersant, and can reduce the amount of adhesive used in conventional positive electrode slurries, satisfying the requirement for high dispersion of the positive electrode slurry and avoiding the problem of a decrease in the specific capacity of the battery due to a decrease in the content of the positive electrode active material.
[0006] Specifically, in a first aspect, the present application provides a dispersant for lithium ion batteries, the dispersant comprising a structural unit A derived from a solvent-philic monomer, a structural unit B derived from a conjugated diene monomer, and a structural unit C derived from a highly adhesive monomer, the solvent-philic monomer comprising one or two of N-vinylpyrrolidone and an acrylamide monomer, and the highly adhesive monomer comprising one or two of an ethylenically unsaturated nitrile monomer and an acrylate monomer.
[0007] The conjugated diene monomer provides the dispersant with a structural unit B that acts as a molecular skeleton, imparting a certain degree of flexibility to the molecular chain of the dispersant and imparting low electrolyte swelling to the dispersant. The solvent-philic monomer provides the dispersant with a structural unit A that has high affinity with the solvent of the positive electrode slurry (e.g., N-methylpyrrolidone (NMP), N,N-dimethylformamide (DMF), etc.), improving the compatibility of the dispersant with the solvent of the positive electrode slurry. The highly adhesive monomer allows the dispersant to have a structural unit C of a nitrile group and / or an ester group polar group, which generates a strong intermolecular interaction with the particles in which the dispersant is dispersed (positive electrode active material particles, conductive material particles, etc.), and the dispersant is easily adsorbed to the interface between the surface of the dispersed particles and the solvent, achieving an excellent dispersion effect in the positive electrode slurry of a lithium ion battery, preventing re-agglomeration of the dispersed particles, and shortening the dispersion time and reducing the amount of dispersant used. In addition, when the positive electrode slurry is dried, the dispersant bonds between the dispersed particles and between the dispersed particles and the current collector, acting as an adhesive, thereby preventing a decrease in the mass proportion of the positive electrode active material in the positive electrode slurry.
[0008] Therefore, the dispersant has both dispersing and adhesive properties, and ensures that the positive electrode active material, conductive agent, etc. achieve excellent dispersion effect in the positive electrode slurry of the lithium ion battery. At the same time, by partially or completely replacing the adhesive in the positive electrode slurry, the content of the positive electrode active material in the positive electrode plate manufactured with the positive electrode slurry is kept basically unchanged, and the problem of a decrease in the energy density of the battery due to the addition of a dispersant can be avoided.
[0009] In some embodiments of the present application, the dispersant includes a copolymer simultaneously containing the above-mentioned structural unit A, structural unit B, and structural unit C. The copolymer may include any one or more of random, block, alternating, and graft copolymer structures.
[0010] In some embodiments of the present application, when calculated based on the total amount of the dispersant, the molar ratio of the structural unit A is 5% to 50%, the molar ratio of the structural unit B is 30% to 90%, and the molar ratio of the structural unit C is 1% to 30%. In this way, the dispersant has a certain degree of solvent affinity, affinity for the particles to be dispersed, and flexibility, and can achieve a high dispersion effect.
[0011] In some embodiments of the present application, the acrylamide monomers include one or more of acrylamide, methylacrylamide, N,N-dimethylacrylamide, N-methylolacrylamide, N-butoxymethylacrylamide, N-(hydroxymethyl)methacrylamide, and N-butoxymethylmethacrylamide, and the like.
[0012] In some other embodiments of the present application, the solvent-philic monomer is N-vinylpyrrolidone. Compared to acrylamide-based monomers, N-vinylpyrrolidone has high structural stability and higher affinity for NMP, the most common solvent in positive electrode slurries.
[0013] In an embodiment of the present application, the number of carbon atoms of the conjugated diene monomer is 4 or more, for example, 4 to 12. Exemplary conjugated diene monomers may include one or more of 1,3-butadiene, isoprene, 2,3-dimethyl-1,3-butadiene, 2-chloro-1,3-butadiene, 1,3-pentadiene, 1,3-hexadiene, 1,3-decadiene, 2-methyl-1,5-heptadiene, and the like.
[0014] In an embodiment of the present application, the ethylenically unsaturated nitrile monomer includes one or more of acrylonitrile, α-methacrylonitrile, α-ethylacrylonitrile, butenenitrile (e.g., 3-butenenitrile, 2-butenenitrile), 2-methyl-2-butenenitrile, 2-methyl-3-butenenitrile, 4-methyl-3-valeronitrile, α-chloroacrylonitrile, α-bromoacrylonitrile, 2-ethoxyacrylonitrile, and 3,3-dimethoxy-2-acrylonitrile.
[0015] In an embodiment of the present application, the acrylate-based monomer includes one or more of acrylic acid alkyl ester, methacrylic acid alkyl ester, acrylic acid hydroxyalkyl ester, methacrylic acid hydroxyalkyl ester, etc. Specifically, exemplary acrylate-based monomers may include, but are not limited to, methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, propyl acrylate, propyl methacrylate, butyl acrylate, butyl methacrylate, tert-butyl acrylate, tert-butyl methacrylate, 2-ethylhexyl acrylate, 2-ethylhexyl methacrylate, dodecyl acrylate, dodecyl methacrylate, 2-hydroxyethyl acrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl acrylate, 2-hydroxypropyl methacrylate, glycidyl acrylate, glycidyl methacrylate, etc.
[0016] In some embodiments of the present application, the highly adhesive monomer is an ethylenically unsaturated nitrile-based monomer. Compared to acrylate-based monomers, ethylenically unsaturated nitrile-based monomers have higher polarity and better dispersing and adhering properties to positive electrode active material particles, conductive agent particles, etc.
[0017] In some embodiments of the present application, the dispersant is formed by polymerizing a monomer raw material including the above-mentioned solvent-philic monomer, conjugated diene monomer, and highly adhesive monomer. In other embodiments of the present application, the dispersant may be obtained by sequentially polymerizing the monomer raw materials and hydrogenating them. By hydrogenating the polymer obtained by polymerizing the monomer raw materials, the double bonds in the polymer obtained by polymerizing the monomer raw materials can be reduced, and the anti-oxidation ability of the dispersant at high voltage can be enhanced.
[0018] In an embodiment of the present application, the weight average molecular weight of the dispersant is 100,000 to 600,000. A dispersant having a weight average molecular weight within this range can have good mechanical properties such as a certain strength and good flexibility, and can be easily used in subsequent processing. For example, the weight average molecular weight of the dispersant may be 150,000, 200,000, 300,000, 350,000, 400,000, 450,000, 500,000, 550,000, or 600,000.
[0019] The dispersant according to the first aspect of the present application has both dispersing and adhesive properties, and therefore can ensure that the positive electrode active material and conductive agent can be highly dispersed in the positive electrode slurry of a lithium-ion battery in a short time, and can increase the solid content of the positive electrode slurry, thereby improving the manufacturing efficiency and product yield of the positive electrode plate. At the same time, the dispersant can partially or completely replace the conventional adhesive in the positive electrode slurry, ensure the capacity of the battery without reducing the mass proportion of the positive electrode active material in the positive electrode plate, and improve the flexibility of the positive electrode plate.
[0020] In a second aspect, a method for producing a dispersant for a lithium ion battery according to the present application includes the steps of: The method includes a step of polymerizing a monomer raw material including a solvent-philic monomer, a conjugated diene monomer, and a highly adhesive monomer, the solvent-philic monomer including one or two of N-vinylpyrrolidone and an acrylamide monomer, and the highly adhesive monomer including one or two of an ethylenically unsaturated nitrile monomer and an acrylate monomer.
[0021] In some embodiments of the present application, the method further includes a step of hydrogenating the polymer formed by polymerizing the monomer raw material. In other words, the method for producing a dispersant includes a step of polymerizing the monomer raw material to obtain a dispersant precursor, and hydrogenating the dispersant precursor. The double bonds of a part or all of the dispersant precursor obtained by polymerizing the monomer raw material can be reduced by a hydrogenation reaction to enhance the anti-oxidation ability of the dispersant at high voltage.
[0022] In some embodiments of the present application, the hydrogenation reaction may be carried out using a noble metal, such as Pt, as a catalyst and hydrogen as the reducing agent.
[0023] In some embodiments of the present application, the ratio of the solvent-philic monomer is 5% to 50%, the ratio of the conjugated diene monomer is 40% to 90%, and the ratio of the highly adhesive monomer is 1% to 20%, calculated based on the total mass of the monomer raw materials. In other embodiments of the present application, the ratio of the solvent-philic monomer is 5% to 30%, the ratio of the conjugated diene monomer is 50% to 80%, and the ratio of the highly adhesive monomer is 5% to 20%, calculated based on the total mass of the monomer raw materials.
[0024] The polymerization method is not particularly limited, and may be, for example, a solution polymerization method, an emulsion polymerization method, a suspension polymerization method, or a bulk polymerization method, and in some embodiments of the present application, the polymerization reaction is performed using a solution polymerization method. The solution polymerization method includes a step of dissolving the monomer raw material and an initiator in a solvent, polymerizing the raw material at a certain temperature, and subjecting the resulting reaction liquid to solid-liquid separation and drying.
[0025] The initiator may be a thermal initiator and / or a photoinitiator, for example, a thermal initiator. As the thermal initiator, one or more of aqueous initiators such as potassium persulfate, sodium persulfate, and ammonium persulfate, or one or more of oil-based initiators such as azobisisobutyronitrile, azobisisoheptonitrile, and benzoyl peroxide can be used. At this time, the temperature of the polymerization reaction may be 40°C to 80°C, and the time of the polymerization reaction may be 2h to 24h. The aqueous initiator or oil-based initiator can be selected based on the monomer raw material and the solvent used.
[0026] In some embodiments of the present application, in the solution polymerization process, a chain transfer agent may be added to the solvent to control the molecular chain length of the resulting polymer. Exemplary chain transfer agents include ethyl acetate, butyl acetate, acetone, diethyl carbonate, methyl tert-butyl ether, isopropyl alcohol, ethanol, methanol, 1-dodecanethiol, etc.
[0027] The method for producing a dispersant according to the second aspect of the present application is simple and easy to operate, has low energy consumption, allows control of the reaction degree, and is suitable for industrial production.
[0028] A third aspect of the present application provides a positive electrode slurry, the positive electrode slurry including a positive electrode active material, a conductive agent, a dispersant, and a solvent, the dispersant being the dispersant according to the first aspect of the present application or the dispersant produced by the production method according to the second aspect of the present application.
[0029] Since the dispersant has both dispersing and adhesive functions, the positive electrode slurry does not need to contain a common adhesive in the battery field. In this case, it is understood that the dispersant completely replaces the adhesive. In some embodiments of the present application, the mass fraction of the dispersant in the positive electrode slurry does not exceed 5%.
[0030] Of course, in other embodiments of the present application, the positive electrode slurry may include an adhesive, and the sum of the mass fractions of the dispersant and the adhesive in the positive electrode slurry does not exceed 5% to avoid reducing the mass fraction of the positive electrode active material in the positive electrode material layer.
[0031] The above positive electrode active material, adhesive and conductive agent are common choices in the battery field. The adhesive may be one or more selected from polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyvinyl alcohol (PVA), styrene butadiene rubber (SBR), polyacrylonitrile (PAN), polyimide (PI), poly(acrylic acid) (PAA), polyacrylate, polyolefin, sodium carboxymethyl cellulose (CMC) and sodium alginate. The positive electrode active material may be at least one of lithium iron phosphate, lithium manganese phosphate, lithium manganese iron phosphate, lithium vanadium phosphate, lithium cobalt phosphate, lithium cobalt oxide (LiCoO2), lithium manganate, lithium nickel oxide, lithium nickel cobalt oxide, lithium nickel manganate, and nickel cobalt manganese (NCM) ternary material, nickel cobalt aluminum (NCA) ternary material. The conductive agent may include, but is not limited to, at least one of carbon nanotubes, carbon black and graphene. The conductive agent may have a functional group such as a carboxyl group or a hydroxyl group on the surface thereof so as to be dispersed in the positive electrode slurry. The dispersant has good affinity for both the positive electrode active material particles and the conductive agent particles.
[0032] The positive electrode slurry according to the third aspect of the present application has a high solid content, in particular a high content of the positive electrode active material, and has good dispersibility, is less likely to settle, and can be left for a long period of time.
[0033] A fourth aspect of the present application further provides a lithium ion battery, the lithium ion battery including a positive electrode plate including a current collector and a positive electrode material layer provided on the current collector, the positive electrode material layer including a positive electrode active material, a conductive agent, an adhesive, and a dispersant, the dispersant being the dispersant described in the first aspect of the present application or the dispersant manufactured by the manufacturing method described in the second aspect of the present application. The lithium ion battery further includes a negative electrode plate, a separator and an electrolyte located between the negative electrode plate and the positive electrode plate. Note that the negative electrode plate, the separator, the electrolyte, and the like are all general structures of a battery, and description thereof will be omitted here.
[0034] Furthermore, the positive electrode material layer of the lithium ion battery can be formed by applying and drying the positive electrode slurry according to the third embodiment of the present application. The positive electrode slurry has a high solid content and a small amount of solvent, and can be dried in a short time to obtain a positive electrode plate, improving the manufacturing efficiency of the positive electrode plate, and the drying time is short, so that the positive electrode plate is less likely to crack and the yield is high. In addition, the positive electrode plate has good flexibility and is easy to assemble into a battery. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0035] The following description is an exemplary embodiment of the present application, and it is to be noted that those skilled in the art may make some improvements and modifications without departing from the principles of the present application, and these improvements and modifications are also deemed to be within the scope of protection of the present application.
[0036] The present invention will now be further described with reference to specific examples. EXAMPLES
[0037] The method for producing a dispersant for lithium ion batteries includes the steps of: The process includes the steps of dissolving N-vinylpyrrolidone, 1,3-butadiene, and acrylonitrile in N,N-dimethylformamide (DMF) in a mass ratio of 40:40:20, adding an initiator azobisisobutyronitrile and a chain transfer agent 1-dodecanethiol, polymerizing at 60°C for 4 hours under a pressure of 4 MPa, cooling to stop the reaction, washing and drying the resulting reaction product to obtain dispersant 1', and subjecting dispersant 1' to a hydrogenation treatment to obtain dispersant 1. The measured weight average molecular weight of dispersant 1 is 500,000.
[0038] The manufacturing method of the positive electrode plate includes the steps of dissolving 1.5 g of adhesive PVDF in 40 g of NMP (N-methylpyrrolidone), adding 0.5 g of the above-mentioned dispersant 1 after sufficient dissolution, and stirring for 20 min; adding 20 g of carbon nanotube dispersion liquid (solvent is NMP, solid content is 5 wt%), and stirring for 20 min; finally adding 97 g of lithium iron phosphate positive electrode active material, and continuing to stir for 1.5 h to obtain a positive electrode slurry; applying the positive electrode slurry to an aluminum foil, and drying at 130°C for 30 min to form a positive electrode material layer, thereby completing the manufacture of the lithium iron phosphate positive electrode plate. EXAMPLES
[0039] The method for producing a dispersant for lithium ion batteries includes the steps of: The process includes dissolving N-vinylpyrrolidone, 1,3-diene, and 2-methyl-2-butenenitrile in DMF at a mass ratio of 5:80:15, adding an initiator azobisisobutyronitrile and a chain transfer agent 1-dodecanethiol, polymerizing at 60°C for 4 hours under a pressure of 4 MPa, cooling to stop the reaction, washing and drying the resulting reaction product to obtain dispersant 2', and subjecting dispersant 2' to hydrogenation treatment to obtain dispersant 2. The measured weight average molecular weight of dispersant 2 is 600,000.
[0040] In the manufacturing method of the positive electrode plate, 0.5g of the dispersant 1 in Example 1 was replaced with 1.5g of the dispersant 2, and 1.5g of the adhesive PVDF was replaced with 0.5g of PVDF, and the rest was the same as in Example 1. EXAMPLES
[0041] The method for producing a dispersant for lithium ion batteries includes the steps of: The process includes the steps of dissolving N-vinylpyrrolidone, 1,3-butadiene, and butyl acrylate in DMF at a mass ratio of 30:65:5, adding azobisisobutyronitrile as an initiator and isobutanol as a chain transfer agent, polymerizing at 60°C for 4 hours under a pressure of 4 MPa, cooling to terminate the reaction, washing and drying the resulting reaction product to obtain dispersant 3. The measured weight average molecular weight of dispersant 3 is 150,000.
[0042] In the manufacturing method of the positive electrode plate, 0.5 g of the dispersant 1 in Example 1 was replaced with 1 g of the dispersant 3, and 1.5 g of the adhesive PVDF was replaced with 1 g of PVDF, and the rest was the same as in Example 1. EXAMPLES
[0043] The method for producing a dispersant for lithium ion batteries includes the steps of: The process includes the steps of dissolving N-vinylpyrrolidone, 1,3-butadiene, and butyl acrylate in DMF at a mass ratio of 40:40:20, adding azobisisobutyronitrile as an initiator and isobutanol as a chain transfer agent, polymerizing at 60°C for 4 hours under a pressure of 4 MPa, cooling to stop the reaction, washing and drying the resulting reaction product to obtain dispersant 4', and subjecting dispersant 4' to hydrogenation treatment to obtain dispersant 4. The measured weight average molecular weight of dispersant 4 is 550,000.
[0044] In the manufacturing method of the positive electrode plate, 0.5g of the dispersant 1 in Example 1 was replaced with 1.5g of the dispersant 4, and 1.5g of the adhesive PVDF was replaced with 0.5g of PVDF, and the rest was the same as Example 1. ( Reference Example 1 )
[0045] The method for producing a dispersant for lithium ion batteries includes the steps of: The process includes dissolving acrylamide, isoprene, and α-ethylacrylonitrile in DMF at a mass ratio of 10:80:10, adding azobisisobutyronitrile as an initiator and ethyl acetate as a chain transfer agent, polymerizing at 60°C for 4 hours under a pressure of 4 MPa, cooling to stop the reaction, washing and drying the resulting reaction product to obtain dispersant 5', and subjecting dispersant 5' to hydrogenation treatment to obtain dispersant 5. The measured weight average molecular weight of dispersant 5 is 400,000.
[0046] The manufacturing method of the positive electrode plate is as follows: 0.8g of adhesive PVDF is dissolved in 30g of NMP, and after it is fully dissolved, 0.4g of dispersant 5 is added and stirred for 20min; 10g of carbon nanotube dispersion (solvent is NMP, solid content is 5wt%) and 1.3g of carbon black are added as conductive agents and stirred for 20min; and finally, 97g of positive electrode active material NCM811 (LiNi 0.8 Co 0.1 Mn 0.1 O2) and stirring for 2 h to obtain a positive electrode slurry; and coating the positive electrode slurry on an aluminum foil and drying at 130° C. for 30 min to form a positive electrode material layer, thereby completing the manufacture of an NCM ternary positive electrode plate. EXAMPLES
[0047] The method for producing a dispersant for lithium ion batteries includes the steps of: The process includes the steps of dissolving N-vinylpyrrolidone, 1,3-hexadiene, and acrylonitrile in dioxane in a mass ratio of 15:80:5, adding an initiator azobisisobutyronitrile and a chain transfer agent 1-dodecanethiol, polymerizing at 60°C for 4 hours under a pressure of 4 MPa, cooling to terminate the reaction, washing and drying the resulting reaction product to obtain dispersant 6', and subjecting dispersant 6' to hydrogenation treatment to obtain dispersant 6. The measured weight average molecular weight of dispersant 6 is 300,000.
[0048] In the method for producing a positive electrode plate, Reference Example 1 0.4g of Dispersant 5 was replaced with 0.6g of Dispersant 6, 0.8g of Adhesive PVDF was replaced with 0.6g of PVDF, and the rest Reference Example 1 is the same as: ( Reference Example 2 )
[0049] The method for producing a dispersant for lithium ion batteries includes the steps of: The process includes the steps of dissolving N-methylolacrylamide, 1,3-butadiene, and acrylonitrile in DMF at a mass ratio of 10:75:15, adding an initiator azobisisobutyronitrile and a chain transfer agent ethyl acetate, polymerizing at 60°C for 4 hours under a pressure of 4 MPa, cooling to stop the reaction, washing and drying the resulting reactant to obtain dispersant 7', and subjecting dispersant 7' to hydrogenation treatment to obtain dispersant 7. The measured weight average molecular weight of dispersant 7 is 600,000.
[0050] In the method for producing a positive electrode plate, Reference Example 1 0.4g of Dispersant 5 was replaced with 0.8g of Dispersant 7, 0.8g of Adhesive PVDF was replaced with 0.4g of PVDF, and the rest Reference Example 1 is the same as:
[0051] In order to highlight the beneficial effects of the present invention, the following Comparative Examples 1-2 are set out. Comparative Example 1
[0052] Comparing the positive electrode plate of Comparative Example 1 with the positive electrode plate of Example 1, the main difference is that when manufacturing a lithium iron phosphate positive electrode plate, no dispersant is added, the amount of PVDF used is 2 g, and the amount of solvent used is increased.
[0053] Specifically, the manufacturing method of the lithium iron phosphate positive plate of Comparative Example 1 includes the steps of dissolving 2 g of adhesive PVDF in 50 g of NMP and thoroughly dissolving it, adding 20 g of an NMP dispersion of carbon nanotubes (solid content is 5 wt%) and stirring for 20 min, finally adding 97 g of lithium iron phosphate positive electrode active material and continuing to stir for 3 h to obtain a positive electrode slurry, coating the positive electrode slurry on an aluminum foil and drying it at 130°C for 30 min to form a positive electrode material layer, thereby completing the manufacture of the lithium iron phosphate positive plate. Comparative Example 2
[0054] Comparing the ternary positive electrode plate of Comparative Example 2 with the ternary positive electrode plate of Example 2, the main difference is that when manufacturing the NCM ternary positive electrode plate, no dispersant is added, the amount of PVDF used is 1.2 g, but the amount of solvent used is increased.
[0055] Specifically, the method for producing the ternary positive plate of Comparative Example 2 includes the steps of dissolving 1.2 g of adhesive PVDF in 40 g of NMP and dissolving it sufficiently, adding 10 g of carbon nanotube dispersion (solid content 5 wt%) and 1.3 g of carbon black as a conductive agent, stirring for 20 min, and finally adding 97 g of positive electrode active material NCM811 (LiNi 0.8 Co 0.1 Mn 0.1 O2) and stirring for 3 h to obtain a positive electrode slurry; and coating the positive electrode slurry on an aluminum foil and drying at 130° C. for 30 min to form a positive electrode material layer, thereby completing the manufacture of an NCM ternary positive electrode plate.
[0056] To advantageously support the beneficial effects of the present application, the results of the viscosity and solid content of the positive electrode slurry, the content of the positive electrode active material in the positive electrode material layer, and the test results of the peel strength of the positive electrode plate for each example and comparative example are summarized in Table 1 below. [Table 1]
[0057] The viscosity of the positive electrode slurry in Table 1 above is measured using a rheometer with the reference model number of Anton Paar MCR 302. The flexibility of the positive electrode plate is observed by the naked eye after folding the positive electrode plate in half. The peel strength of the positive electrode plate is tested by the pressure-sensitive adhesive tape peel test method according to the GB / T 2792-1998 standard.
[0058] As can be seen from Table 1, the viscosities of the positive electrode slurries in Examples 1 to 4 are close to that of Comparative Example 1, and , Reference Examples 1, 2 The viscosity of the positive electrode slurry in Example 5 is close to that in Comparative Example 2, and both can meet the manufacturing requirements of the corresponding electrode plates. , Reference Examples 1, 2 As can be seen from the comparison between Example 1 and Comparative Example 2, when the content of the positive active material in the positive electrode material layer is unchanged, the positive electrode slurry containing the dispersant according to the embodiment of the present application has a high solid content, a high dispersion effect, a short preparation time for the positive electrode slurry, and a small amount of adhesive PVDF is used, which indicates that the dispersant according to the present application can partially replace PVDF and perform adhesive function. In addition, the peel strength of the positive electrode plate of the embodiment of the present application is also higher than that of the corresponding comparative example.
[0059] In addition, as can be seen from a comparison between Example 1 and Example 4, when the mass ratio of each component in the monomer raw material is the same, the dispersant made from acrylonitrile has a slightly higher peel strength of the positive electrode plate than the dispersant made from acrylate.
[0060] The above examples merely show some embodiments of the present application, and although the description is specific and detailed, it should not be understood as limiting the scope of the claims of the present application. However, those skilled in the art can make some further modifications and improvements without departing from the concept of the present application, and all of these fall within the scope of protection of the present application. Therefore, the scope of protection of the patent of the present application should be based on the scope of the attached claims.
Claims
1. A dispersant for lithium ion batteries, comprising a structural unit A derived from a solvent-philic monomer, a structural unit B derived from a conjugated diene monomer, and a structural unit C derived from a highly adhesive monomer, The dispersant for lithium ion batteries, wherein the solvent-philic monomer comprises N-vinylpyrrolidone, and the highly adhesive monomer comprises one or both of an ethylenically unsaturated nitrile monomer and an acrylate monomer.
2. Calculated based on the total amount of the dispersant, the molar ratio of the structural unit A is 5% to 50%, the molar ratio of the structural unit B is 30% to 90%, and the molar ratio of the structural unit C is 1% to 30%. The dispersant according to claim 1.
3. The ethylenically unsaturated nitrile monomer includes one or more of acrylonitrile, α-methacrylonitrile, α-ethylacrylonitrile, butenenitrile, 2-methyl-2-butenenitrile, 2-methyl-3-butenenitrile, 4-methyl-3-valeronitrile, α-chloroacrylonitrile, α-bromoacrylonitrile, 2-ethoxyacrylonitrile, and 3,3-dimethoxy-2-acrylonitrile; The acrylate monomer includes one or more of an alkyl acrylate ester, an alkyl methacrylate ester, a hydroxyalkyl acrylate ester, and a hydroxyalkyl methacrylate ester; 3. The dispersant of claim 1 or 2, wherein the conjugated diene monomer comprises one or more of 1,3-butadiene, isoprene, 2,3-dimethyl-1,3-butadiene, 2-chloro-1,3-butadiene, 1,3-pentadiene, 1,3-hexadiene, 1,3-decadiene and 2-methyl-1,5-heptadiene.
4. The dispersant according to any one of claims 1 to 3, wherein the weight average molecular weight is 100,000 to 600,000.
5. A method for producing a dispersant for lithium ion batteries, comprising a step of polymerizing a monomer raw material including a solvent-philic monomer, a conjugated diene monomer, and a highly adhesive monomer to obtain a dispersant for lithium ion batteries, wherein the solvent-philic monomer includes N-vinylpyrrolidone, and the highly adhesive monomer includes one or two of an ethylenically unsaturated nitrile monomer and an acrylate monomer.
6. 6. The method of claim 5, further comprising the step of hydrogenating the polymer formed by polymerizing the monomer feedstock.
7. The method according to claim 5 or 6, wherein, calculated based on the total mass of the monomer raw materials, the ratio of the solvent-philic monomer is 5% to 50%, the ratio of the conjugated diene monomer is 40% to 90%, and the ratio of the highly adhesive monomer is 1% to 20%.
8. A positive electrode slurry comprising a positive electrode active material, a conductive agent, a dispersant, and a solvent, the dispersant being the dispersant according to any one of claims 1 to 4.
9. 10. The cathode slurry of claim 8, wherein a mass fraction of the dispersant in the cathode slurry does not exceed 5%.
10. A method for producing a positive electrode slurry, comprising: The positive electrode slurry contains a positive electrode active material, a conductive agent, a dispersant, and a solvent, A method for producing a positive electrode slurry, comprising the method for producing a dispersant according to any one of claims 5 to 7.
11. The method for producing a positive electrode slurry as described in claim 10, wherein the mass fraction of the dispersant in the positive electrode slurry does not exceed 5%.
12. A lithium ion battery comprising: a positive electrode plate including a current collector and a positive electrode material layer disposed on the current collector, the positive electrode material layer including a positive electrode active material, a conductive agent, and a dispersant, the dispersant being the dispersant according to any one of claims 1 to 4.
13. A method for manufacturing a lithium ion battery, comprising the steps of: The lithium ion battery includes a positive electrode plate including a current collector and a positive electrode material layer disposed on the current collector, the positive electrode material layer including a positive electrode active material, a conductive agent, and a dispersant; A method for producing a lithium ion battery, comprising the method for producing a dispersant according to any one of claims 5 to 7. A method for producing a lithium ion battery.
Citation Information
Patent Citations
Composition for electric power storage device, slurry for electrode for electric power storage device, electrode for electric power storage device, and electric power storage device
JP2019197695A
Conductive material dispersion and utilization thereof
JP2020187866A
Dispersant, conductive material dispersion, and slurry for electrode film
JP2021122751A
Water soluble polymer binder for lithium ion battery
US20110168956A1
Positive electrode for secondary battery, and secondary battery
WO2013129658A1